A Modelling Study of the Dynamics of Sulphide Heap Leach Processes with a View to Improved and Novel Applications - Jochen Petersen; David G. Dixon (International Mineral Processing Congress, 2003)
"Although heap leaching may be perceived as a somewhat low-tech route for the extraction of low-grade minerals, the underlying physical, chemical and biological processes are in fact extremely complex. There has been increased interest in heap leaching of sulphide minerals in recent years with the advent of controlled bio-heap leaching, and the need to mine more marginal ore deposits.A detailed investigation into the dynamics of heap leach processes has provided much insight into the underlying complexities, and has led to the development of a sophisticated modelling tool, HeapSim. Some of the sub-processes that are modelled include mineral kinetics, particle size effects, bacterial growth, oxidation and adsorption, gas adsorption, pore diffusion, bulk advection, gas balance and heat conservation. The interplay of these various sub-processes is illustrated in the paper.Two case studies are presented which illustrate specific features of the model for different applications and how these have helped to identify key areas of concern. The first is focussed on chalcocite heap bioleaching, which shows that by nature of the reaction the process is strongly dependent on the initial supply of acid to the mineral site. In heaps this acid supply can be severely limited by the rate of diffusion from channels of flowing solution into stagnant zones of the heap, whereas in narrow-bore laboratory columns this effect is not observed."